THE INFLUENCE OF WORKLOAD AND COMPETENCE ON THE SERVICE QUALITY OF INTERCITY TRAVEL DRIVERS IN EAST NUSA TENGGARA - Andrias Umbu Tuku Anabuni; Irmina Linda Dewiaty (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: Intercity transportation in East Nusa Tenggara plays an important role in community mobility. In the transportation service industry, drivers play a direct role in determining the quality of service passengers. However, in practice, there are constraints, including complaints about driver behaviour, delays, and uncomfortable service conditions. Two factors that are likely to influence this condition are excessive workload and varying driver competence. Therefore, this study aims to analyze the influence of workload and competence on the service quality of intercity travel drivers in the region.Methods: This research uses a quantitative approach, employing a survey distributed to several travel drivers serving the Kupang–Soe intercity route in East Nusa Tenggara. The independent variables in this study are workload and competence, while the dependent variable is service quality. The data analysis technique used is multiple linear regression to measure the influence of each variable both partially and simultaneously.Results: The research findings indicate that the workload, competence, and service quality of intercity travel drivers in East Nusa Tenggara are in the very high category. Drivers face heavy work demands, but generally possess good technical competence, knowledge, and professional attitude, enabling them to provide quality service. Inferential analysis proves that workload and competence, both individually and simultaneously, significantly affect service quality, with competence being the most dominant factor.Although High workloads can potentially lower service quality, the drivers' experience and sense of responsibility are able to maintain service performance. Practically, these findings confirm the importance of proportional workload management and continuous competency development to maintain and improve the quality of intercity travel services. Keywords: Competence On The Service Quality, Influence Of Workload, Intercity Travel Drivers